Conceptualising Rugby League performance within an ecological dynamics framework: Providing direction for player preparation and development - Scott, T. J.; Sanctuary, C. E.; Tredrea, M. S.; Gray, A. J. (Sports Medicine - Open, 2021)
Across team sports, it is critically important to appropriately define, evaluate and then aptly describe individual and team performance. This is of particular significance when we consider that performance models govern the direction of player preparation (short term) and development (long term) frameworks. Within the context of rugby league, this has traditionally been undertaken through hierarchical and linear processes. Such approaches have resulted in research and performance analysis techniques which aim to support these operational outcomes. Yet, these methods may deliver limited application on how or why match-play unfolds and therefore might be sub-optimal in providing insights to truly support coaches. In this paper, we propose the conceptualisation of rugby league performance through the lens of ecological dynamics, which may offer a different view to this traditional approach. We propose that this approach eliminates the silos of disciplinary information (e.g. technical, physical and medical) that may currently exist, allowing for a holistic approach to performance, preparation and development. Specifically, we consider that through the implementation of this ecological approach, all performance coaches (technical, physical and medical) may (co-)design learning environments that more collaboratively develop players for rugby league match-play. As a result, we put forward a new rugby league performance model from which preparation and development programs can be anchored toward. We conclude the paper by offering practical examples where these concepts are contextualised within the landscape familiar to practitioners working within rugby league.